Architecture on The Imah Panggung and Babaritan Tradition as A Space Spirit in Kampung Kranggan, Bekasi, Indonesia - Abdullah Ali; Siti Rukayah; Agung Budi Sardjono; Sudarmawan Juwono (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2022)
AbstractThe current environmental crisis has made the theme of local wisdom related to the architecture and traditions of the archipelago a severe concern. Efforts to explore and rediscover functions, forms, meanings, and philosophies have been neglected due to the massive urban modernization. As an area directly adjacent to the capital city of Jakarta, the city of Bekasi is indeed inseparable from the problems of urbanization. This research focuses on the Imah Panggung and the Babaritan tradition (alms of the earth) in Kampung Kranggan, which persists today. Using qualitative methods, namely conducting in-depth observations and interviews with traditional elders, conducting descriptive analysis based on data and field findings. It can be concluded that the Imah Panggung and the Babaritan tradition have a solid relationship not only in terms of activity and function of space but also the philosophical meaning and heritage of knowledge and methods from ancestors, which are still very relevant today. The relationship between human beings, humans and nature, and humans and God are represented in the Imah Panggung architecture and the Babaritan ritual procession as the spirit of space in Kampung Kranggan.